Genotypic prevalence of human papillomavirus infection during normal pregnancy: A cross-sectional study - Kim, Yun Hwan; Park, Joong Shin; Norwitz, Errol R.; Park, Jeong Woo; Kim, Sun Min; Lee, Seung Mi; Park, Chan-Wook; Kim, Byoung Jae; Koo, Ja Nam; Oh, Ig Hwan; Song, Yong Sang (The journal of obstetrics and gynaecology research, 2014)
Aim Genital human papillomavirus (HPV) infection is a necessary factor in most cases of cervical cancer, but malignant transformation requires the presence of additional cofactors such as pregnancy. Little is known about the effect of pregnancy on genital HPV carriage. We therefore analyzed the prevalence and genotypic patterns of genital HPV infections in normal pregnancies. Methods The prevalence of HPV infection was measured in 960 consecutive normal pregnant or post‐partum women by HPV‐DNA chip analysis of cervical swabs. Data were analyzed by trimester and adjusted for sociodemographic, reproductive and reported sexual history. Results The overall prevalence of HPV infection in the population was 24.3%. High‐risk HPV genotypes were detected in 68.2% of infected subjects, including HPV 16 (18.7%), 39 (16.4%), 53 (10.1%), and 56 (9.4%). High‐risk HPV genotypes were significantly more prevalent in the second trimester (23.8%) compared with the other periods (first trimester, 13.2%; third trimester, 17.4%; post‐partum, 15.1%; P = 0.010). However, the high‐risk HPV genotypes 16 or 18 were detected most frequently in the third trimester (7.2%) as compared to the other periods (first trimester, 2.9%; second trimester, 5.2%; post‐partum, 2.1%; P = 0.03). After adjusting for confounding variables, overall HPV infection (odds ratio = 1.84, 95% confidence interval = 1.24–2.75) and high‐risk HPV genotypes (odds ratio = 1.94, 95% confidence interval = 1.23–3.05) were significantly more common in the second trimester. Conclusion The second trimester may be the most vulnerable period in high‐risk HPV infections, which necessitates future investigations.